An Oral History of the Special Olympics in China Volume 3 Finding and Keeping a Job - Alford, William P.; Liao, Mei; Cui, Fengming (Economy and Social Inclusion, Creating a Society for All, 2020)
This open access book brings together oral histories that record the experiences of individuals with intellectual disabilities in Shanghai as they participate in their careers. Employees with intellectual disabilities describe their experiences seeking, attaining, and maintaining employment. Their managers, colleagues, and family members also provide keen insight into the challenges and opportunities these individuals have encountered in the process of securing employment. An appendix provides a compilation of employment policies related to people with intellectual disabilities, particularly with respect to Shanghai.